KAJIAN PEMBENTUKAN KELEMBAGAAN UNTUK PENGENDALIAN KONVERSI DAN PENGEMBANGAN LAHAN, PERAN DAN FUNGSINYA - Ikhwanuddin Mawardi (Jurnal Teknologi Lingkungan, 2006)
Forest convertion are a major cause of land destruction in Java Island. Farm land and watershed are eroded by the swift changes to income sources and levels that accompany industrial plantation work, civil community, shopping center etc. Government must be integral with effective agricultural land preservation programs, plans institution of conversion land and policies (i.e. erosion management, ground water protection, buffering, etc.)